2014
DOI: 10.1002/bdra.23220
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal inflammation in the pathogenesis of bronchopulmonary dysplasia

Abstract: Exposure to hyperoxia, invasive mechanical ventilation and systemic/local sepsis are important antecedents of postnatal inflammation in the pathogenesis of bronchopulmonary dysplasia (BPD). This review will summarize information obtained from animal (baboon, lamb/sheep, rat and mouse) models that pertain to the specific inflammatory agents and signaling molecules that predispose a premature infant to BPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 159 publications
1
68
0
1
Order By: Relevance
“…A number of investigators have reported the association of an inflammatory influx with subsequent development of BPD in preterm infants with lung disease 2,1619 . Elastase activity and neutrophil counts in tracheal aspirates of intubated preterm infants in the first week of life are higher in infants that subsequently develop BPD 20 .…”
Section: Discussionmentioning
confidence: 99%
“…A number of investigators have reported the association of an inflammatory influx with subsequent development of BPD in preterm infants with lung disease 2,1619 . Elastase activity and neutrophil counts in tracheal aspirates of intubated preterm infants in the first week of life are higher in infants that subsequently develop BPD 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The latter point could be explained by the hypothesis that the esophageal afferent neural pathways might be more reactive to decreases in pH among patients with BPD because of their increased inflammatory state. 30 The activation of vagal afferents could trigger airway efferent responses resulting in protective reflexes such as esophagoglottal closure and pharyngoglottal closure. 31 Another explanation of our findings could rely on the fact that infants with BPD compared with infants without BPD received a significantly lower intake of fluids at the time of pH-MII because of their chronic pulmonary condition, resulting in a lower buffering capacity of milk.…”
Section: Discussionmentioning
confidence: 99%
“…Натомість, ризик виникнен-ня важчих форм БЛД не був пов'язаний з меншим терміном гестації або масою тіла при народженні, важчим загальним станом на момент народження і госпіталізації у відділення інтенсивної терапії новонароджених, а також важчим первинним за-хворюванням легень. Ці дані свідчать про важли-ву роль інфекційних процесів і пов'язаних з ними запальних реакцій у формуванні важчих форм БЛД в немовлят, які після народження потребува-ли інтубації і ШВЛ, що узгоджується з сучасною концепцією хронічного легеневого ураження у новонароджених [15,16].…”
Section: обговоренняunclassified